THE GAME CHANGER; UNDERSTANDING HOW BRAND IMAGE AND CUSTOMER SATISFACTION INFLUENCES BRAND LOYALTY. A STUDY OF SAMSUNG MOBILE PHONES IN PAKISTAN - Dr. Ahmed MuneebMehta, Dr. Zargham Ullah Khan, Jaffar Mahmood Butt, Maham Tariq, Rimsha Khalid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
It is important to understand how brand image and customer satisfaction influence brand loyalty of Samsung mobile phones. ''A Samsung mobile is a progressive and mysterious product that is actually five years in front of some other mobile phones.'' It considered a strong competitor of the overall industry among all the brands of mobile phones in Pakistan. Samsung mobile organization is the worldwide market pioneer just as in Pakistan among mobile phone organizations(Mehta, Ahmad, and Ali 2019). The purpose of this research is to identify how brand image and customer satisfaction influences brand loyalty of Samsung mobile phone. Its major purpose is to focus the youthful individuals who are utilizing Samsung brand and well- educated individuals with the goal that they give significant responses to inquire about questionnaires. The research data is collected from 100 participants of Lahore. The result analysis shows that there is positive association between brand image and customer satisfaction on brand loyalty of a Samsung mobiles.